Investigating of Language Errors in the Field of Morphology in Scientific Articles of State High School Student - Fitriani, Ria; Pohan, Jusrin Efendi; Syahfitri, Dian (Jurnal Educatio FKIP UNMA, 2024)
This research was motivated by students' problems in speaking in writing according to linguistic rules. Language errors that often occur in writing or written works that do not comply with linguistic rules include affixation, reduplication, diction and compositum. This can be seen from the written work written by high school students due to the students' lack of knowledge about language. The main aim of this research aims to describe the forms of language errors in the field of morphology in scientific articles made by Seribu Bukit State High School students. The research data is in the form of 27 student scientific articles. The method used in this research is a qualitative descriptive method. The analysis technique used is the test technique. The test is in the form of a scientific article. Students are asked to write scientific articles. The results of this research show that the forms of morphological errors found in scientific articles of class not standard. The form of error in the field of reduplication lies in its redundant/pleonic use. The form of a composite error lies in the procedure for writing it. The findings of this research show that language errors in the morphological aspect are found in grammatical errors, diction errors, affixation errors, and composite errors.